A chemotaxonomic and serotaxonomic investigation of some Pinus species : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Botany at Massey University - Butcher, Stephen Mark (Massey University, 1982)
A relatively simple and rapid method is presented for the extraction of protein from adult tissues of four species of Pinus. Protein was extracted using a low pH mixture containing reducing agents, thiols, and polyvinylpolypyrrolidone. The protein interferring components were separated and removed from the protein solution on a Sephadex column. Protein extracted using this method was found to be useful for separation and analysis by electrophoresis and isoelectric focussing, for enzyme analysis following separation by these techniques, and for antibody production used in serological techniques. These techniques were evaluated for their ability to provide information on the taxonomy of the Pinus species examined. The high resolution technique of isozyme analysis by isoelectric focussing, and the serological analysis were found to be most useful. The relationship between these species suggested by the results support the division of the genus Pinus into two subgenera, Haploxylon and Diploxylon, as suggested by Koehne (1893). The results also support the classification suggested by Shaw (1914) but no evidence was found to support the classification suggested by Pilger (1926).
Keywords: Pine; Chemotaxonomy